Risk Management Strategies using Precision Agriculture Technology to Manage Potato Late Blight. (1st March 2017) - Liu, Yangxuan; Langemeier, Michael R.; Small, Ian M.; Joseph, Laura; Fry, William E.
Abstract : Core Ideas: The benefits of adopting precision farming technology was investivated in scheduling fungicide applications to manage potato late blight. The precision farming technology is the preferred method to schedule fungicide applications in terms of disease suppression, net return per 0.41 ha, and risk‐adjusted net return. The increased adoption of the precision farming technology would help manage late blight, limit potential crop losses, and improve net returns. Precision agriculture has emerged as a revolutionary technology, which transforms farming related data into useful information for agricultural decision‐making. This paper compares precision farming technology with calendar‐based approach in scheduling fungicide applications to manage potato ( Solanum tuberosum L.) late blight disease. Three fungicide scheduling strategies were evaluated: calendar‐based strategy, BlightPro decision support system based strategy (DSS‐based strategy), and unsprayed control. Using results from 14 yr of computer simulation experiments for 59 locations in the United States, we constructed distributions of net return to all costs excluding fungicide cost and application cost per 0.41 ha (net return per 0.41 ha) for the calendar‐based and DSS‐based strategies at each location. These distributions were then compared using three risk management methods: stochastic dominance, stochastic dominance with respect to a function, and stochastic efficiency with respect to a function. The DSS‐based strategy was identified as the most effective approach to manage late blight in terms of disease suppression, net return per 0.41 ha, and risk‐adjusted net return. Results indicate that the DSS‐based strategy is the preferred method to schedule fungicide applications. Under high disease pressure circumstances, the economic benefits to potato growers of adopting the precision agriculture technology ranged from US30 to 573 per 0.41 ha. For risk neutral individuals, who are concerned about the difference between average net return per 0.41 ha, the benefits ranged from 30 to 305 per 0.41 ha. Except for growers raising the moderately resistant potato cultivars, more risk averse individuals tended to benefit more from adopting the precision agriculture technology, with benefits ranging from 38 to 573 per 0.41 ha.